Calibrating Communication Simulator for Connected Vehicle Applications. Issue 1 (2nd January 2016) - Su, Peng; Lee, Joyoung; Park, Byungkyu "Brian"
Abstract : Research efforts focused on the connected vehicle (CV) technology applications typically assume perfect communications among the vehicles and between the vehicles and the roadside equipment. However, a few studies, including this one, pointed out that the wireless communications experience packet drops, which might lead to a serious downgrade of the safety critical CV applications. Thus, the wireless communication simulators used to emulate the communications performance need to be properly calibrated to replicate the real-world vehicular communication environments. This study calibrated an NCTUns simulator for the dedicated short range communications (DSRC) of CV technology using the DSRC field test data executed on an instrumented intersection at the Turner–Fairbank Highway Research Center. Physical layer parameters (e.g., data rate and transmission power) as well as channel models are calibrated. The calibration applied a Latin hypercube sampling technique to generate multiple combinations of parameter sets. The calibrated NCTUns simulator produced much more realistic outputs than the uncalibrated one. Then a signalized intersection was simulated in a case study to further investigate the packet drops of DSRC-based CV communications. The results indicated that there were significant packet drops, requiring further research before implementing safety critical CV applications.